2011
DOI: 10.1061/(asce)cc.1943-5614.0000076
|View full text |Cite
|
Sign up to set email alerts
|

Nonlaminated FRP Strap Elements for Reinforced Concrete, Timber, and Masonry Applications

Abstract: Advances in material technology allow for the exploration of new structural forms and systems. In recent years, fibre reinforced polymers (FRPs) have emerged as candidate materials for civil engineering applications and the use of FRPs in construction has been an area of growing interest. Unidirectional high strength FRPs are well-suited for use as tensioning elements but anchorage details present a challenge. An alternative is to self-anchor the FRP tensioning element by winding thin layers of material around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It was concluded that this method would be more effective for large-span beams, and it was recommended that the sum of the initial and additional shear stress from loading between the CFRP strips and the concrete should be limited to the shear stress given in Approach 3 in fib (2001). Lees and Winistörfer (2011) reviewed the non-laminated CFRP strap systems and their potential for the use of self-anchored FRP tension elements with a variety of civil engineering materials. It was shown that when the strap is non-laminated, as opposed to laminated, higher efficiencies can be achieved.…”
Section: The Rehabilitation Of Rc and Pc Bridge Beams In Flexure Usinmentioning
confidence: 99%
“…It was concluded that this method would be more effective for large-span beams, and it was recommended that the sum of the initial and additional shear stress from loading between the CFRP strips and the concrete should be limited to the shear stress given in Approach 3 in fib (2001). Lees and Winistörfer (2011) reviewed the non-laminated CFRP strap systems and their potential for the use of self-anchored FRP tension elements with a variety of civil engineering materials. It was shown that when the strap is non-laminated, as opposed to laminated, higher efficiencies can be achieved.…”
Section: The Rehabilitation Of Rc and Pc Bridge Beams In Flexure Usinmentioning
confidence: 99%
“…Winistoerfer et al [ 18 , 19 ] studied the pin-loaded looped CFRP strap and suggested it can be used as practical tensile elements since the load can transfer through the pins without the requirement of additional anchoring systems. Lees et al [ 20 ] and Hoult et al [ 21 , 22 ] conducted experiments to analyze the enhancement of shear capacity of reinforced concrete due to CFRP strap. Fan et al [ 23 , 24 ] investigated the distribution of stress, failure mechanism and bearing efficiency by finite element (FE) models.…”
Section: Introductionmentioning
confidence: 99%
“…The prestressed carbon FRP (CFRP) straps 6 used in this study consist of unidirectional carbon fibers embedded in a thermoplastic resin to create a 12 mm (0.47 in.) wide by 0.16 mm (0.0063 in.)…”
Section: Introductionmentioning
confidence: 99%